The Road - Villaroel, Carmina; Agustin, Marvin; Ramos, Rhian; Forteza, Barbie; Trinidad, TJ; Laranas, Yam; Adlawan, Aloy; Gozon-Abrogar, Annette ([Quezon City] GMA Films, 2012)
A Twelve year old cold case is reopened when three teens are missing in an abandoned road. In the course of the investigation, deeper and more gruesome. Stories of abduction and murders are discovered. After more than two decades, the secrets of the haunted road may finally be revealed.
DVD
Executive producer, Annette Gozon-Abrogar ; screenplay, Aloy Adlawan, Yam Laranas ; director, Yam Laranas .
Carmina Villaroel, Marvin Agustin, Rhian Ramos, Barbie Forteza, TJ Trinidad.
Keywords: The Road (Motion picture).; Horror films; Feature films